PERBEDAAN KEPUASAN PELANGGAN TERHADAP METODE RESERVASI ONLINE TRAVEL AGENT DAN WEBSITE HOTEL DI NAGOYA MANSION HOTEL DAN RESIDENCE BATAM - ", Mernaliana; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research we gather are to know the differences from the guest’s satisfaction on the reservation between booking from various online travel agents and the hotel website for Nagoya Mansion Hotel.This research are using the methods of quantities description focusing on the topic we discuss. The amount we gather from our guest are as many as 100 guests. Furthermore the technique for gathering its data for this research by observing and documentation. We have put the data into a likert scale with four indicators. These indicator are hotel convenience, hotel price, hotel loyalist and hotel knowledge which these evaluation of the guest’s satisfactory on the reservation made by booking from various online travel agents and the hotel website which personally booked by the hotel guest. With the research that we have gathered, there are not much differences with the guest’s satisfactory on the two methods for reservation.The median satisfaction of guests who make Reservation at Online Travel Agents are is obtained in the amount of 38,18. While the median of the satisfaction of guests who make reservation via the hotel website is 37,46. (9,24 > 0,71) Its conclusion is H0 is rejected and HA is received, which means there is a relationship between the Online Travel Agent Reservation Method and Website Hotel Reservation Method.Keywords: Room Reservastion, Guests Satisfaction, Reservation